Phenomena induced by photoionisation in gas-filled hollow-core photonic crystal fibres - Tani, Francesco; Köhler, Johannes; Suresh, Mallika; Schade, Daniel; Köttig, Felix; Russell, Philip St. John (International Conference on Transparent Optical Networks, 2020)
The optical properties of hollow-core photonic crystal fibre (HC-PCF) can be conveniently tailored by modifying the transverse microstructure and selecting the species and pressure of the gas filling the hollow regions. Additionally, absorption of light by the gas can result in transient changes in refractive index, with characteristic timescales varying from a few hundred femtoseconds to hundreds of microseconds. Understanding the dynamics of these effects is essential for scaling the power and the repetition rate of laser pulse trains launched into HC-PCF, is relevant for pump-probe experiments, and can suggest new ways of controlling the guiding properties of these fibres. Here we review our recent studies, showing measurements of the temporal evolution of local changes in refractive index and describing the novel experimental techniques we developed to investigate the effects.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Nonlinear optics; Photonic crystal fibres